Indodax Demonstrates Better Usability Than Tokocrypto Based on SUS and EEG Analysis - Rachmad Fadillah; Tranggono Tranggono; Mega Cattleya Prameswari Anissa Islami (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Cryptocurrency investment applications have become increasingly important in supporting digital financial transactions and mobile-based investment activities. Specific Background: Usability plays a critical role in cryptocurrency applications because users interact with complex and high-risk transaction systems requiring effective navigation, efficiency, and cognitive comfort. Knowledge Gap: Previous usability studies on cryptocurrency applications have predominantly relied on subjective approaches such as System Usability Scale (SUS) and conventional usability testing, while the integration of Electroencephalography (EEG) for physiological validation remains limited. Aims: This study aimed to evaluate and compare the usability of the cryptocurrency investment applications Indodax and Tokocrypto based on ISO 9241-11 by integrating performance measurement, System Usability Scale (SUS), and Electroencephalography (EEG). Results: The findings showed that Indodax achieved higher usability performance with an SUS score of 71.5, effectiveness of 98%, and efficiency of 0.059 goal/second, while Tokocrypto obtained an SUS score of 56.75, effectiveness of 74%, and efficiency of 0.036 goal/second. EEG analysis revealed dominant Alpha waves in Indodax, indicating lower cognitive load and more comfortable interaction, whereas Tokocrypto demonstrated dominant Beta waves associated with higher cognitive burden and user stress. Several usability problems in Tokocrypto were identified, including asset navigation, transaction history visibility, and transaction amount selection. Novelty: This study integrates subjective usability assessment, performance measurement, and EEG-based physiological analysis in cryptocurrency application evaluation. Implications: The results provide practical guidance for interface redesign and support the development of more cognitively efficient cryptocurrency investment applications. Highlights: Indodax achieved higher task completion rates and faster interaction performance than Tokocrypto. Dominant Alpha brainwave patterns indicated lower cognitive burden during Indodax interaction sessions. Asset filtering, transaction records, and nominal selection created major interaction difficulties in Tokocrypto. Keywords: Usability, ISO 9241-11, SUS, EEG, Crypto, Indodax, Tokocrypto